“I Authored This Book in the Absence of My Slave”: Enslaved East Africans and the Production of Occult Knowledge across the Omani Empire - AlMaazmi, Ahmed Yaqoub (Monsoon, 2024)
What role did enslaved East Africans play in producing and transmitting the occult sciences between East Africa and Oman? This article explores the relationship between enslaved East Africans and the occult sciences in the works of Nās.ir bin Abī Nabhān (1778–1846), a jurist and practitioner of the occult sciences who lived between Oman and East Africa. It argues that enslaved East Africans were instrumental in producing and disseminating valuable occult knowledge. The analysis informs how occult knowledge operated and circulated between the Arabian and African coasts, animated in occultist idioms, and was written in Arabic and Swahili. Moreover, it explores how East African and Omani actors articulated occultist knowledge by paying attention to the interlinkages between power dynamics and knowledge hierarchies during the expansion of the Bu Saidi Empire in the nineteenth century. This study explores uncharted waters in a transoceanic sphere by tracing translation processes and nonEuropean imperial knowledge production in the Indian Ocean world.
Keywords: Esclavage – Zanzibar; Occultisme – Oman

Asking Sentient Trees: Arabian Translations of East African Magic and Swahili Language in the Omani Empire - Almaazmi, Ahmed Yaqoub (2024)
Keywords: Moeurs et coutumes – Zanzibar; Occultisme – Oman